Insurance and Climate Change : Scoping Paper - Gurenko, Eugene (World Bank, Washington, DC, 2013)
The purpose of this paper is to provide a conceptual framework, along with concrete illustrations, that will aid the UNFCCC process in incorporating market-based insurance mechanisms in the arsenal of proposed global climate adaptation tools. A key objective is to define the role insurance can play in helping households, businesses, and countries better adapt to the main known manifestations of climate change, such as weather extremes. The paper defines risk assessment, and outlines the conceptual framework used throughout the analysis. It provides an overview of the significance of public and private partnerships in insuring weather related losses, as well as best practices. It concludes with an overview of lessons learned, and identifies opportunities for market-based insurance strategies in the global adaptation for climate change. A major realization was the importance of establishing a transparent, well-defined policy on government subsidies after disasters, so that individuals can gauge their risks in weather related disasters, and might be encouraged to buy private insurance.